Revisiting the Civil Society and Democratic Governance in Africa: Present or Absent in Nigeria? - Ogunwa, Samuel Adetola; Florence Adeseeke Ogunwa (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political UMA), 2023)
The civil society midwife democratic government in 1999. They fought for it. Although, some died in the process of agitating for democracy, and the fundamental human rights and rule of law are firmly entrenched including the freedom of association, free movement, speech among others. The paper argues that today’s democratic government was worked for but those who work for it did not participate in the transition program since the military in their characteristics are maradonic particularly that of General Ibrahim Gbadamosi Babangida keep transition program in perplexity and continuous. The failure of the leaders and members of civil organizations to participate is responsible for the crisis of governance. Those elected into governments across the states including the federal government largely masquerading behind politics as governance output. The paper is of the view that the civil society organization in the country cannot claim irresponsible to Nigerians, since they ushered in democratic rule, therefore, efforts must be geared towards validating the purpose of democracy and dividends of democratic governance in Nigeria.